Cognitive Factors Influencing Second Language learning - GHEDEIR BRAHIM, Mohammed (University of Eloued جامعة الوادي, 2016)
Second language learners are different. It is proved that they learn with different speed and different results. The general factors that influence second language learning according to Ellis (1985) are intelligence and aptitude, and cognitive learning styles. This paper aims in the first place to elaborate cognitivism and its implications to the second language learning by analyzing the three views on second language acquisition (the behaviorist view, the innatist view, and the interactionist view). In the second place, the present study describes language proficiency and the influence of cognition on second language acquisition. Then the study sheds light on intelligence and aptitude, and cognitive learning styles as key cognitive factors influencing second language (L2) learning.
THE SECOND NATIONAL CONFERENCE ON LANGUAGE, MIND AND LEARNER'S COGNITIVE CAPACITIES March, 7th/8th 2016 University of Eloued
Keywords: cognition, second language acquisition, innatist, behaviorist, interactionist, intelligence, aptitude, learning styles.